Supporting collaborative development using process models: a tooled integration‐focused approach1. Issue 10 (6th February 2014) - Kedji, Komlan Akpédjé; Lbath, Redouane; Coulette, Bernard; Nassar, Mahmoud; Baresse, Laurent; Racaru, Florin; Huang, Liguo; Armbrust, Ove
ABSTRACT Collaboration in software engineering projects is usually intensive and requires adequate support by well‐integrated tools. However, process‐centered software engineering environments (PSEE) have traditionally been designed to exploit integration facilities in other tools, while offering themselves little to no such facilities. This is in line with the vision of the PSEE as the central orchestrator of project support tools. We argue that this view has hindered the widespread adoption of process‐based collaboration support tools by incurring too much adoption and switching costs. We propose a new process‐based collaboration support architecture, backed by a process metamodel, that can easily be integrated with existing tools. The proposed architecture revolves around the central concepts of 'deep links' and 'hooks'. Our approach is validated by analyzing a collection of open‐source projects, and integration utilities based on the implemented process model server have been developed. Copyright © 2014 John Wiley & Sons, Ltd.